Burkholderia cepacia infection in children without cystic fibrosis: a clinical analysis of 50 cases - Shi, Huixuan; Chen, Xianrui; Chen, Lili; Zhu, Bizhen; Yan, Weiyuan; Ma, Xiaobo (Frontiers in Pediatrics, 2023)
Background: Burkholderia cepacia (B. cepacia) is an emerging pathogen of nosocomial infection in pediatric patient carrying cystic fibrosis. The clinical diagnosis and treatment of B. cepacia infection remains poorly studied. This study outlined the risk factors, antimicrobial susceptibility, and clinical characteristics aiming to improve the treatment of B. cepacia infection. Methods: A retrospective study was conducted based on the 50 cases infection caused by B. cepacia in children without cystic fibrosis, which were diagnosed in the First Affiliated Hospital of Xiamen University, from January 1st, 2011 to December 31st, 2021. Results: A total of 50 children were infected with B. cepacia, of whom 68% had an underlying health condition, such as cardiovascular disease (23.5%), respiratory disease (17.6%), nervous system disease (14.7%), and neoplastic disease (14.7%). At the onset of B. cepacia infection, 42 (84%) pediatric patients were in an intensive care unit (ICU), 33 (66%) underwent endotracheal intubation, and 32 (64%) had a central venous catheter (CVC). In addition, hospital-acquired cases were 46 (92%), and healthcare-acquired cases were 4 (12%). The most common infectious sites of B. cepacia were the respiratory tract (68%), followed by the blood (20%), and the urinary tract (12%). It indicated that B. cepacia was the most sensitive to ceftazidime (95.65%), followed by trimethoprim-sulfamethoxazole (88.68%), meropenem (82.98%), cefepime (77.78%), and levofloxacin (55.85%). The drug resistance rate of piperacillin-tazobactam, minocycline, aztreonam, cefoperazone-sulbactam and ceftriaxone was higher than 55%. 38 cases were cured or improved, eight had treatment terminated, and four died. Conclusion: B. cepacia is an opportunistic pathogen normally found in immunocompromised pediatric patients and highly likely to lead to drug resistance. Nosocomial B. cepacia infections occured mostly in patients in the ICU based on our observations. The surveillance of B. cepacia infections including changing epidemiology and increasing resistance of the microorganism is still very important. Treatment with effective antibiotics such as ceftazidime, meropenem, trimethoprim-sulfamethoxazole is associated with a favorable prognosis.